The origin and evolution of Baeyer-Villiger monooxygenases (BVMOs): an ancestral family of flavin monooxygenases - Mascotti, María Laura (2015)
The Baeyer-Villiger Monooxygenases (BVMOs) are enzymes belonging to the "Class B" of flavin monooxygenases and are capable of performing exquisite selective oxidations.These enzymes have been studied from a biotechnological perspective, but their physiologicalsubstrates and functional roles are widely unknown. Here, we investigated the origin,taxonomic distribution and evolutionary history of the BVMO genes. By using in silicoapproaches, 98 BVMO encoding genes were detected in the three domains of life: Archaea,Bacteria and Eukarya. We found evidence for the presence of these genes in Metazoa(Hydra vulgaris, Oikopleura dioica and Adineta vaga) and Haptophyta (Emiliania huxleyi) forthe first time. Furthermore, a search for other "Class B"monooxygenases (flavoproteinmonooxygenases -FMOs - and N-hydroxylating monooxygenases -NMOs) was conducted.These sequences were also found in the three domains of life. Phylogenetic analysesof all "Class B" monooxygenases revealed that NMOs and BVMOs are monophyletic,whereas FMOs form a paraphyletic group. Based on these results, we propose that BVMOgenes were already present in the last universal common ancestor (LUCA) and their currenttaxonomic distribution is the result of differential duplication and loss of paralogous genes.